2011
DOI: 10.1037/a0024493
|View full text |Cite
|
Sign up to set email alerts
|

On the plasticity of the survival processing effect.

Abstract: Nairne, Thompson, and Pandeirada (2007) discovered a strong and rather general memory advantage for word material processed in a survival-related context. One possible explanation of this effect conceives survival processing as a special form of encoding: Nature specifically "tuned" our memory systems to process and remember fitness-relevant information. We tested this explanation by studying whether the survival processing effect is robust against encoding manipulations that do not affect the fitness relevanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
197
4
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(217 citation statements)
references
References 34 publications
(63 reference statements)
11
197
4
5
Order By: Relevance
“…Thus, perhaps the relevant proximate mechanism for intentional processing of survival materials, like that suggested for incidental processing of materials for their survival value, is the balance between item-specific and relational processing that contribute to both the elaboration and discriminability of traces in memory. As Kroneisen andErdfelder (2011, p. 1554) argued, maybe "it is not the evolutionary significance of survival per se that explains the survival processing effect. Rather, the degree to which survival processing invites elaborative, distinctive forms of encoding would predict the mnemonic benefit of survival processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, perhaps the relevant proximate mechanism for intentional processing of survival materials, like that suggested for incidental processing of materials for their survival value, is the balance between item-specific and relational processing that contribute to both the elaboration and discriminability of traces in memory. As Kroneisen andErdfelder (2011, p. 1554) argued, maybe "it is not the evolutionary significance of survival per se that explains the survival processing effect. Rather, the degree to which survival processing invites elaborative, distinctive forms of encoding would predict the mnemonic benefit of survival processing.…”
Section: Discussionmentioning
confidence: 99%
“…More generally, item-specific and relational processing contribute to trace elaboration and discrimination (distinctiveness), both of which have been found to account for survival processing effects in a variety of experiments. For example, Kroneisen and Erdfelder (2011) demonstrated that when both richness (elaborateness) of encoding and item distinctiveness were controlled, performance differences between survival processing and control tasks disappeared. Thus, perhaps the relevant proximate mechanism for intentional processing of survival materials, like that suggested for incidental processing of materials for their survival value, is the balance between item-specific and relational processing that contribute to both the elaboration and discriminability of traces in memory.…”
Section: Discussionmentioning
confidence: 99%
“…Kroneisen and Erdfelder (2011) argued that the survival processing scenario produced high levels of elaboration which subsequently generated the mnemonic benefit, hence when a shorter survival scenario was utilised, the advantage disappeared. Experiment 1 demonstrated evidence of the survival processing advantage using a shortened survival scenario.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Nairne's (2005Nairne's ( , 2010 advocacy of memory as a system evolved to enhance survival (clearly a future-oriented enterprise; e.g., Klein et al, 2011) has resulted in a highly active program of research exploring the effects of encoding conditions (survival versus non-survival) on measures of retention (e.g., Burns, Hwang, & Burns, 2011;Butler, Kang, & Roediger, 2009;Kang, McDermott, & Cohen, 2008;Klein, 2012;Klein, Lax, et al, 2010;Klein, Robertson, et al, 2010, Klein et al, 2011Kroneisen & Erdfelder, 2011;Nairne & Pandeirada, 2008;Nairne, Pandeirada, Gregory, & Van Arsdall, 2009;Otgaar, Smeets, & van Bergen, 2010;Soderstorm & McCabe, 2011;Weinstein, Bugg, & Roediger, 2008; for recent reviews, see Howe & Otgaar, 2013;Klein, in press). Another approach to memory that emphasizes its futureoriented aspects is that of memory in its prospective capacities (for review, see Brandimonte, Einstein, & McDaniel, 1996).…”
Section: Discussionmentioning
confidence: 99%